Bonding social ties: relative human capital and immigrant network choices. Issue 7 (19th May 2022) - Chuatico, Georgina; Haan, Michael
ABSTRACT: Upon migrating to a new country, immigrants will often turn to their ethnic communities for support, forming bonding social ties in the process. However, there are also those who form bridging ties by reaching outside of one's immediate ethnic group. The social position occupied by individuals in society is maintained and reproduced by the cultural and human capital they possess, wherein the socialised dispositions, conceptions, and level of education unite and differentiate social groups. As a result, immigrant network formation occurs not only on the lines of ethnicity, but also on cultural and human capital. In this paper, we use the Longitudinal Survey of Immigrants to Canada to investigate how immigrants use social ties upon arrival to Canada. We find that newcomers with lower levels of human capital will be more likely to bond, whereas higher human capital newcomers will often bridge.